Micropartículas lipídicas sólidas obtidas por spray drying para liberação intraocular de ibuprofeno - Pere, Cristiane Patricia Pissinato [UNESP] (2014)
Vitreoretinal diseases are serious disease of the posterior segment of the eye. They are characterized by important inflammatory manifestations and if it is not treated properly they develop into irreversive blindness. Although major advances have occurred in the medical and tecnhological fiels, the treatment of deseases that affecting the posterior segment of the eye remains a challenge, because of the anatomical and physiological barrier's eyes that hinder the entrance of exogenous substances. An alternative is the local drug delivery in drug delivery systems, whom are able to prolong release of the drug within the therapeutic range systems, reducing the number of administrations and providing more confort and safety for patient. The aim of this work was the development and characterization ibuprofen loaded solid lipid microparticles obtained by spray drying method for a potential intraocular application. Hydrogenated soy phosphatidylcholine SLM modified by glyceryl monostearate or stearyl alcohol, added 15 to 30% of ibuprofen were obtained. According to scanning electron microscopy, the MLS showed mostly spherical and homogeneous morphologies. The infrared analysis, differential scanning calorimetry and x-ray diffraction suggest that the drug is solubilized in the MLS array. These results also showed that the method was able to reduce the crystallinity of the drug and other components of the microparticle, favoring the encapsulation efficiency and the subsequent diffusion of the drug release study. The release study showed a busrt release followed by a sustained release, that may be useful not only in the treatment of postoperative cataract surgery and in the treatment of diseases vitreoretinianas itself.